Fatal neonatal respiratory failure in an infant with congenital hypothyroidism due to haploinsufficiency of the NKX2-1 gene: alteration of pulmonary surfactant homeostasis. Issue 6 (28th June 2010) - Kleinlein, Barbara; Griese, Matthias; Liebisch, Gerhard; Krude, Heiko; Lohse, Peter; Aslanidis, Charalampos; Schmitz, Gerd; Peters, Jochen; Holzinger, Andreas
Abstract : Defects of the NKX2-1 gene, encoding thyroid transcription factor-1, cause brain-thyroid-lung syndrome (MIM 610978), characterised by benign hereditary chorea, congenital hypothyroidism and respiratory disease. The case of a term infant with mild primary congenital hypothyroidism and neonatal persistent respiratory failure with fatal outcome at 10 months of age despite continuous ventilatory support is described. Congenital defects of genes known to disturb surfactant protein and lipid homeostasis ( SFTPB, SFTPC, ABCA3 ) were excluded. Hypothyroidism prompted sequencing of NKX2-1, which revealed a heterozygous 29 bp deletion (c.278_306del29) disrupting the affected allele. Analysis of bronchoalveolar lavage fluid demonstrated an abnormally low amount of surfactant protein C (SP-C) in relation to SP-B, and low levels of surfactant phospholipids, indicating disturbance of SP and lipid homeostasis as a consequence of NKX2-1 haploinsufficiency. NKX2-1 haploinsufficiency may lead to lethal respiratory failure of the newborn due to disruption of pulmonary surfactant homeostasis. NKX2-1 gene analysis should be considered when investigating irreversible respiratory insufficiency of the newborn.